Origins of the Imperial and Secular Power according Ockham’s Political Thought - C. R. de Souza, José Antônio de (Anales del Seminario de Historia de la Filosofía, 2010)
In this article, based on the most important William of Ockham’s O. Min. (c. 1285 – 1347) writings, we analyze his ideias concerning the origins of the imperial and secular power. Founded in the Paul’s doctrine omnis potestas a Deo, but enlarged, per homines, and also on the ideas of his Franciscan brothers which lived before, which articulated the concepts of proprietas and domininum, in order to explain the human origins of the both, on the one hand, Ockham refuses not only the hierocratic theory, but also Marsilius of Padua thought about this subject, and, on the other hand, he offers his contribution for this subject, according with which, nor the Empire neither the Estates are completely subordinated to the Church, nor the Church is subordinated for the secular power, because, referring its origins, both, Church and Estates are different origins, the first has a divine proceeding, the others, are immediately a human provenance and, because, in its specific spheres of action the spiritual power and the secular power do not depend one of the other and vice versa.